“Ripping off the band-aid”: uncovering future health care professionals' “fractured knowledge” about sexual and reproductive health - Mejia, Angie; Nyhus, Kara; Burley, Tessie; Myhre, Alexis; Montes, Marcela; Osiecki, Kristin; Randolph, Anita C. (Frontiers in Reproductive Health, 2024)
Background: Research has shown the role of identity on future health professionals' confidence and competence in addressing the sexual and reproductive health (SRH) needs of their patients. While there has been some work in increasing the sexual health literacy of future providers via various curricular approaches and clinical-based training, there are research gaps on how social differences impact future healthcare professionals' knowledge and practices around SRH. This article presents research findings on the experiences of US undergraduate students attending a health sciences and health professions campus. Our study aims to understand the perspectives of these students as they pertain to their future career choices in healthcare, with a focus on how their past experiences learning about sex, sexuality, and reproduction impact their current and future professional trajectories. We present a qualitative analysis from 40 in-depth interviews with U.S. undergraduates. The interview questions were designed in collaboration with undergraduate researchers interested in sexual health education. These student researchers collected all the interview data and worked with senior researchers to analyze some of these data. The themes that emerged from the interviews were around experiences with what students perceived as "fractured" sexual and reproductive health (SRH) knowledge they received as children and adolescents. This knowledge shaped essential aspects of their identity as young adults and future healers. Data indicated unique processes implicated in how past as well as present socialization experiences learning about sex, sexuality, and reproduction positions undergraduates in health professions to see young adulthood as a journey of "catching up" on sexual knowledge but also as an ongoing experience of anticipation and planning influencing their career-building journey. The importance of sexual health literacy among healthcare professionals cannot be overstated, as it is vital in providing patient-centered and non-judgmental sexual and reproductive health (SRH) care and services. To date, there is a shortage of studies looking at the impact of sexual health knowledge on healthcare professionals. More research is needed on educational strategies to assist college-aged young adults in healthcare career tracks to "catch up" or "fill in the gaps" in their sexual education journey.